Electronic structure and signature of Tomonaga–Luttinger liquid state in epitaxial CoSb1−x nanoribbons - Rui Lou (Nature Portfolio, 2021)
Abstract Recently, monolayer CoSb/SrTiO3 has been proposed as a candidate harboring interfacial superconductivity in analogy with monolayer FeSe/SrTiO3. Experimentally, while the CoSb-based compounds manifesting as nanowires and thin films have been realized on SrTiO3 substrates, serving as a rich playground, their electronic structures are still unknown and yet to be resolved. Here, we have fabricated CoSb1−x nanoribbons with quasi-one-dimensional stripes on SrTiO3(001) substrates using molecular beam epitaxy and investigated the electronic structure by in situ angle-resolved photoemission spectroscopy. Straight Fermi surfaces without lateral dispersions are observed. CoSb1−x /SrTiO3 is slightly hole doped, where the interfacial charge transfer is opposite to that in monolayer FeSe/SrTiO3. The spectral weight near the Fermi level exhibits power-law-like suppression and obeys a universal temperature scaling, serving as the signature of Tomonaga–Luttinger liquid (TLL) state. The obtained TLL parameter of ~0.21 shows the underlying strong correlations. Our results not only suggest CoSb1−x nanoribbon as a representative TLL system but also provide clues for further investigations on the CoSb-related interface.